The Impact of Credit Market Development on Auditor Choice: Evidence from Banking Deregulation - DE FRANCO, GUS; GUAN, YUYAN; ZHOU, YIBIN; ZHU, XINDONG (Journal of Accounting Research, 2024)
ABSTRACT We exploit the staggered state‐level adoption of the Riegle‐Neal Interstate Banking and Branching Efficiency Act (IBBEA) to examine how banking deregulation and the resulting increase in bank competition affect firms’ auditor choices. We find that an exogenous increase in the degree of interstate branch banking deregulation leads to a reduction in firms’ propensity to engage a Big N or industry expert auditor. This main result, when combined with our cross‐sectional analyses, offers evidence suggesting that deregulation leads to less demand for higher quality auditors because (1) firms have increased access to credit, which reduces the benefits of higher audit quality; (2) entering banks’ lending expertise substitutes for higher quality financial statements; (3) incumbent banks with less lending expertise seek to protect their rents by preferring that borrowers provide lower quality financial statement information; and (4) external stakeholders delegate their monitoring to banks to a greater degree, resulting in less demand for higher quality financial statements. As such, our study sheds light on how the U.S. credit market's infrastructure shapes firms’ auditor choice decisions.